2021
DOI: 10.1177/08948453211039286
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Mentors’ Interpersonal Behaviors and Mentees’ Motivation, Turnover Intentions, Engagement, and Well-Being

Abstract: Using self-determination theory among a sample of student employees, the present cross-sectional study ( N = 358) examines how mentors’ interpersonal behaviors relate to both motivation at work and motivation for a mentoring relationship and how these two contexts of motivation can differentially relate to mentees’ work outcomes. Results revealed that mentors’ need-supportive interpersonal behaviors were associated with greater autonomous motivation at work and in the mentoring relationship and, in turn, to gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 71 publications
1
3
0
5
Order By: Relevance
“…Leur perception relative aux comportements de soutien influence davantage le sentiment de plaisir et de fierté vis-à-vis du travail (motivation autonome au travail), ce qui leur permet de développer des sentiments et des comportements plus positifs au travail (plus de bien-être, plus d’engagement au travail et moins tendance à vouloir quitter le travail). Pris dans leur ensemble, ces résultats vont dans le même sens que les prémisses de la TAD (Ryan & Deci, 2017) et les liens obtenus dans les études antérieures menées au travail (Dagenais-Desmarais et al, 2014; Firzly et al, 2022). Ainsi, les mentors qui instaurent un climat de soutien influencent positivement la qualité de la motivation et le développement professionnel des mentorés.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Leur perception relative aux comportements de soutien influence davantage le sentiment de plaisir et de fierté vis-à-vis du travail (motivation autonome au travail), ce qui leur permet de développer des sentiments et des comportements plus positifs au travail (plus de bien-être, plus d’engagement au travail et moins tendance à vouloir quitter le travail). Pris dans leur ensemble, ces résultats vont dans le même sens que les prémisses de la TAD (Ryan & Deci, 2017) et les liens obtenus dans les études antérieures menées au travail (Dagenais-Desmarais et al, 2014; Firzly et al, 2022). Ainsi, les mentors qui instaurent un climat de soutien influencent positivement la qualité de la motivation et le développement professionnel des mentorés.…”
Section: Discussionunclassified
“…Toutefois, la recherche théorique et empirique soutiennent que plusieurs facteurs contextuels à l’intérieur d’un même milieu peuvent contribuer au bon fonctionnement des individus. L’étude de Firzly et al (2022)—l’une des seules ayant exploré simultanément la motivation pour le travail et la motivation pour la relation de mentorat —est un exemple du rôle que peuvent prendre deux types de motivation qui diffèrent sur le plan contextuel. Les résultats de cette étude ont révélé que la motivation pour le travail et celle pour la relation de mentorat jouent toutes les deux un rôle dans la prédiction de conséquences souhaitables au travail.…”
Section: Le Rôle Du Mentorat En Milieu De Travailunclassified
See 1 more Smart Citation
“…Empirical evidence suggested that work engagement is a strong antecedent of employee turnover intention (Azharudeen and Arulrajah, 2021;Bayode and Duarte, 2022;Bufquin et al, 2021;Gomes and Seruca, 2023;Mallin et al, 2022;Peltokorpi and Allen, 2023). Studies in this domain showed that work engagement as a motivational construct has an inverse relation with workers' intentions to leave (Albrecht and Marty, 2020;Firzly et al, 2021;Memon et al, 2019;Wang, 2020). Individuals with a high level of work engagement form exceptional relationships with their managers/supervisors.…”
Section: Relationship Between Work Engagement and Turnover Intentionmentioning
confidence: 99%
“…3.4 Work engagement as a mediator between behavior-based sales control system and salespersons' job outcomes Salespersons' performance and turnover intentions have gained a lot of attention in prospective sales research and practice (Albrecht and Marty, 2020;Ampofo and Karatepe, 2022;Dugan et al, 2022;Firzly et al, 2021;Memon et al, 2019;Pennbrant and Dåderman, 2021;Wang, 2020). The current research has focused on a salesperson's work engagement as a mediator for varied reasons.…”
Section: Relationship Between Work Engagement and Turnover Intentionmentioning
confidence: 99%